Lingkungan Kerja Fisik dan Non Fisik pada PT. Gemilang Prima Utama - Sutilah Sutilah; Palahudin Palahudin (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The work environment constitutes a critical factor influencing employee effectiveness, particularly in head office functions that rely on administrative accuracy and interdepartmental coordination. In practice, inadequately managed physical facilities and suboptimal workplace relationships may hinder employees’ comfort and work effectiveness. This study aims to describe the conditions of the physical and non-physical work environment and to examine how these conditions relate to employee work effectiveness at the Head Office of PT Gemilang Prima Utama, a construction service company. The research employed a descriptive survey approach involving 35 head office employees as respondents. Data were collected through direct observation, interviews, and structured questionnaires, and analyzed using descriptive percentage analysis. The findings indicate that several aspects of the physical work environment, such as lighting, noise control, and workplace safety, are perceived as generally adequate. However, key supporting facilities including work chairs, air conditioning systems, and internet connectivity remain insufficient. Regarding the non-physical work environment, relationships between supervisors and subordinates are predominantly positive, while relationships among coworkers are perceived as less harmonious. These conditions collectively affect employees’ comfort, coordination, and daily work effectiveness. The study demonstrates that employee effectiveness is shaped by the integrated condition of both physical and non-physical work environments rather than by either aspect in isolation, highlighting the importance of comprehensive workplace management in head office settings within construction service companies.